Analysis of the Clinical Characteristics of Patients with Malignant Neoplasms of the Pancreas Who Received Medical Care in Hospitals in St. Petersburg in the Period from 2015 to 2020 - V. E. Moiseenko; P. A. Ponomarev; A. V. Pavlovsky; D. A. Granov; L. V. Kochorova; N. I. Vishnyakov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The objective of the study was the analysis of the main clinical characteristics identified in patients with malignant neoplasms of the pancreas, who received medical care in healthcare institutions of St. Petersburg in the period from 2015 to 2020.Methods and materials. A continuous study of clinical and statistical data of patients with pancreatic cancer receiving medical care in healthcare institutions of St. Petersburg (of federal and city subordination) for the period from 01.2015 to 02.2020 was carried out. In total, the study included depersonalized medical cards of 2141 patients diagnosed with pancreatic cancer.Results. During the studied period, more than half of the patients diagnosed with cancer of the pancreas received medical care in specialized oncological institutions of city subordination, a third – in federal institutions, 11.3 % – in multidisciplinary city hospitals. The maximum number of cases was in patients of older age groups: 41.7 % – 70 years and over, including 15.4 % – 80 years and over. The majority (39.7 %) of new patients with pancreatic cancer hospitalized in medical institutions of St. Petersburg were diagnosed with stage IV of the disease. The disease, according to examinations, was represented by stage III in 29.7 % of patients at the time of initial hospitalization. The pancreatic cancer was presented with stage III in 20 % of the patients. The disease was registered in 4.4 % of patients at stage I. Stage 0 or carcinoma in situ was diagnosed at initial presentation in 4.7 % of patients. The stage of the disease was not determined in 1.4 % of patients. The tumor was located in the head of the pancreas in 64.4 % of patients. The most common histological type of pancreatic cancer is ductal adenocarcinoma, which was verified in 72.0 % of patients. Type 2 diabetes mellitus was registered in 37 % of patients as concomitant disease.Conclusion. The results of the analysis of clinical and statistical data of patients with pancreatic cancer may become a background for conducting research on the early detection of this neoplasm.